A Comparative Review of Four Photographic Atlases for MicrobiologyA Photographic Atlas for the Microbiology Laboratory, Fourth Edition; Michael J. Leboffe and Burton E. Pierce; (2011). Morton Publishing Company, Englewood, CO. 256 pages.<!--product-->Microbiology: A Photographic Atlas for the Laboratory; Steven K. Alexander and Dennis Strete; (2001). Pearson Education, Inc., Upper Saddle River, NJ. 193 pages.<!--product-->Microbiology Perspectives: A Photographic Survey of the Microbial World, Second Edition; George Wistreich; (2007). Pearson Education, Inc., Upper Saddle River, NJ. 232 pages. - Deborah Tobiason (American Society for Microbiology, 2011)
Review of: four photographic atlases for microbiology, including: A Photographic Atlas for the Microbiology Laboratory, Fourth Edition; Michael J. Leboffe and Burton E. Pierce; (2011) . Morton Publishing Company, Englewood, CO. 256 pages. Microbiology: A Photographic Atlas for the Laboratory ; Steven K. Alexander and Dennis Strete; (2001) . Pearson Education, Inc., Upper Saddle River, NJ. 193 pages. Microbiology Perspectives: A Photographic Survey of the Microbial World , Second Edition; George Wistreich; (2007) . Pearson Education, Inc., Upper Saddle River, NJ. 232 pages. and ASM’s MicrobeLibrary Atlas.